How state pension subsidies undermine equity. (May 2019) - Shuls, James V.; Hitt, Collin; Costrell, Robert M.
When policy advocates debate how best to ensure equity in public education funding, the topic of teacher pension reform rarely comes up. But, in fact, pensions represent a very large and fast-growing source of education spending, much of it distributed in ways that are, in a number of states, anything but equitable. When states subsidize teacher pensions directly, rather than expecting local school systems to fund those pensions themselves, affluent districts tend to benefit the most .